Longmire. The complete fifth season [videorecording (DVD)] - Taylor, Robert, 1963-; Sackhoff, Katee; Phillips, Lou Diamond, 1962- (Warner Bros., 2017)
A sheriff struggles to turn his life around in the wake of his wife's recent passing.